Bits and pieces: A survey characterizing equipment use on the heads of therapeutic/adaptive riding horses in the United States - Sarah Jean Reega; Sarah K. Matlock; Sharon Butler; Kathleen R. Auchmoody; Ann M. Hess; B. Caitlin Peters (Journal of Veterinary Behavior, 2026)

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Hematophagous ectoparasites affect nestling size and physiology, but not apparent survival - Emma N. Stierhoff; Julianna M. Carpenetti; Sarah A. Knutie; Jon W. Wallace; Michael W. Butler (Journal of Ornithology, 2024)

Wildfire and Family Forest Owners: Concern, Advice, and Wildfire Reduction Behaviors from the United States National Woodland Owner Survey - Sarah M Butler; Brett J Butler; Emma M Sass (Forest Science, 2024)
Extreme wildfire is an increasing threat to lives, property, and ecosystems across the United States and many parts of the world. Family forest owners (FFOs) own a large percentage of forestland in the United States, and actions and behaviors on their forestland have a large impact on wildfire prevention and mitigation across the landscape. Using data from the USDA Forest Service’s 2018 National Woodland Owner Survey, we investigated national and regional FFO wildfire attitudes and behaviors. We see that concern for wildfire is relatively high across the United States; however, this concern does not always lead to wildfire reduction activities on the landscape. There is some variation among regions, with concern about wildfire and past wildfire reduction activities highest in the western US (76% and 37%, respectively), followed by the South (63% and 11%, respectively), and lowest in the northern region (50% and 8%, respectively). Understanding these aspects of wildfire and FFOs on a national level provides a broader context for the more focused studies across the country and acts as a launch point for more in-depth research in the future. Study Implications: This study assesses family forest owner (FFO) wildfire concern, information needs, and action, both past and intended, at national and regional levels across the United States. As wildfire is predicted to increase in frequency and severity into the future due to climate change, this research provides a reference line and a launch point for future studies. Understanding current concern levels and landowner characteristics can inform programs and policies aimed at mitigating severe wildfires. For example, the disconnect between concerns and actions can be used as an entry point for motivating additional owners to take steps towards active management. Concentrating efforts in fire-prone areas is important, but seeing that wildfire is a concern of family forest owners across much of the country suggests that this can be an important issue for starting conversations with many owners and possibly increasing their engagement with conservation efforts.

A comparison between field measurements of vapour concentrations of plant protection products and predictions by the BROWSE model - M. Clare Butler Ellis; Edgars Felkers; Sarah Adham; Anne-Kim Vinck; Kathrin Bürling; Neil Morgan (Regulatory Toxicology and Pharmacology, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Studies of Family Forest Owners in the USA: A Systematic Review of Literature from 2000 through 2019 - Brett J. Butler; Sarah M. Butler; Kristin Floress (Small-scale Forestry, 2023)

Social Marketing Works: Results from Ten Years of Tools for Engaging Landowners Effectively Trainings - Katherine Hollins; Purnima Chawla; Sarah M Butler (Journal of Forestry, 2023)
Engaging family forest owners in best practices for land management is essential for maintaining and improving the health of our forests. Yet few natural resource professionals have formal training in how to reach and persuade landowners. The Tools for Engaging Landowners Effectively (TELE) program sought to address this via a program of workshops, which train natural resource professionals to engage and influence landowners by using social marketing principles and techniques. TELE evaluation surveys found that (1) TELE workshop participants understood social marketing concepts and appreciated their relevance and value, (2) they were able to apply these concepts in their work, and (3) those who applied these concepts saw improved project outcomes. Based on these results, we argue that more natural resource professionals should be trained and empowered to use social marketing techniques for engaging landowners and other audiences. Study Implications: Forestry and conservation professionals are often tasked with engaging landowners to help solve conservation challenges, but they rarely have the training to do so effectively. Surveys of professionals trained in social marketing (using commercial marketing principles to reach a public good) showed that the workshops were considered useful, and projects implemented using the learned techniques showed a substantial improvement over standard outreach methods. Based on these data, we call for more widespread and comprehensive adoption of social marketing techniques for engaging landowners and describe what that would entail.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

The multi-element stoichiometry of wet eucalypt forest is transformed by recent, frequent fire - Orpheus M. Butler; James J. Elser; Tom Lewis; Sarah C. Maunsell; Mehran Rezaei Rashti; Chengrong Chen (Plant and Soil, 2020)

Minority Family Forest Owners in the United States - Sarah M Butler; John Schelhas; Brett J Butler (Journal of Forestry, 2020)
Family forest owners own more forestland in the United States than any other group. There have been no national studies of racial and ethnic minority family forest owners in the United States, in spite of increasing attention to diversity in forestry. Using the US Forest Service’s National Woodland Owner Survey data, we sought to better understand minority owners by looking at their characteristics, attitudes, and behaviors. Of the over 4 million family forest ownerships with 10+ ac in the United States, minorities comprise 6.6 percent of the ownerships and own 5.1 percent of the 265 million ac. Although many similarities exist between minority and nonminority owners, such as reasons for owning land and concerns, minority landowners tend to be more regionally located, have smaller forest holdings, are less likely to manage their forests, and are less likely to have participated in assistance programs. Broad insight into the attitudes and behaviors of minority family forest owners can help policymakers, program directors, and outreach coordinators begin to understand the needs of minority landowners, providing this historically underserved group with tools they need to attain their forest management and land-use goals. By increasing minority landowner engagement, we can hopefully slow the loss of land by minority landowners.

The stoichiometric legacy of fire regime regulates the roles of micro‐organisms and invertebrates in decomposition - Orpheus M. Butler; Tom Lewis; Mehran Rezaei Rashti; Sarah C. Maunsell; James J. Elser; Chengrong Chen (Ecology, 2019)
Decadal‐scale increases in fire frequency have the potential to deplete ecosystems of essential nutrients and consequently impede nutrient‐limited biological processes via stoichiometric imbalance. Decomposition, a fundamental ecosystem function and strong driver of future fire occurrence, is highly sensitive to nutrient availability and is, therefore, particularly important in this context. Here we show that 40 yr of quadrennial (4yB) and biennial (2yB) prescribed burning result in severely P‐ and N‐depleted litter stoichiometry, respectively, relative to fire exclusion. These effects exacerbated the nutrient limitation of microbial activities, constraining litter decomposition by 42.1% (4yB) and 23.6% (2yB) relative to unburned areas. However, invertebrate‐driven decomposition largely compensated for the diminished capacity of micro‐organisms under 4yB, suggesting that invertebrates could have an important stabilizing influence in fire‐affected ecosystems. This effect was strongly positively coupled with the strength of microbial P‐limitation and was not obviously or directly driven by fire regime‐induced changes in invertebrate community assemblage. Together, our results reveal that high‐frequency fire regimes promote nutrient‐poor, carbon‐rich ecosystem stoichiometry and, in doing so, disrupt ecosystem processes and modify the relative functionality of micro‐organisms and invertebrates.

Methods for Increasing Cooperation Rates for Surveys of Family Forest Owners - Brett J. Butler; Jaketon H. Hewes; Mary L. Tyrrell; Sarah M. Butler (Small-scale Forestry, 2017)

Family Forest Owner Characteristics Shaped by Life Cycle, Cohort, and Period Effects - Sarah M. Butler; Brett J. Butler; Marla Markowski-Lindsay (Small-scale Forestry, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Extra-tropical atmospheric response to ENSO in the CMIP5 models - Margaret M. Hurwitz; Natalia Calvo; Chaim I. Garfinkel; Amy H. Butler; Sarah Ineson; Chiara Cagnazzo; Elisa Manzini; Cristina Peña-Ortiz (Climate Dynamics, 2014)

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Validation of quantitative trait loci for Ascochyta blight resistance in pea (Pisum sativum L.), using populations from two crosses - Gail M. Timmerman-Vaughan; Tonya J. Frew; Ruth Butler; Sarah Murray; Margy Gilpin; Karla Falloon; Paul Johnston; Michael B. Lakeman; Adrian Russell; Tanveer Khan (Theoretical and Applied Genetics, 2004)